Design Optimization Of A High Frequency Power Transformer For A Switching Power Supply By Genetic Algorithms Approach - Rama Rao, Dr.K.S.; Lai, Yong Lei; Taib, Dr. Soib; Masri, Syafrudin (USM, 2004)
The design optimization of a single-phase high frequency power transformer used in switching power supplies is presented in this paper.